Sustainable intensification of agriculture: the foundation for universal food security - Glenn Denning (npj Sustainable Agriculture)
The Green Revolution approaches in Asia (mainly through intensification) and sub-Saharan Africa (through both intensification and extensification) greatly increased food supply in both regions with environmental costs in both settings. To curb further loss of natural ecosystems and associated land degradation, biodiversity loss, and greenhouse gas (GHG) emissions, sustainable intensification (SI) is redefined as a process in aggregate, comprising a portfolio of interventions at global, regional, and national levels that increase food availability and reduce agriculture’s environmental footprint. To achieve universal food security, SI must be accompanied by complementary investments in market infrastructure, postharvest stewardship, healthy diets, and social protection. The complexity of the food system requires a whole-of-government, multi-sector approach to implementation, enabled by informed, responsive, and courageous leadership.